Measurement of Thalassia testudinum mediation of sediment resuspension and settling using traps and plates in a subtropical estuary, Estero Bay, Florida, USA - Katrina E. Kaack; David Fugate; Serge Thomas (All Earth)
Seagrass meadows are highly productive ecosystems which provide many ecological services to organisms. Seagrass canopies create a hydrodynamically low-energy environment which can increase sediment deposition and reduce resuspension, thus enhancing habitat stability. Direct measurements of sediment deposition usually employ cylindrical traps, but results from this method have been debated. Flat sediment plates are an alternative method that minimise the problems of cylindrical traps but do not measure the exact same processes. Plate traps were used in conjunction with cylindrical traps to measure sediment deposition in a seagrass bed and nearby barren site in Estero Bay, Florida, U.S.A. Sediment plates and cylindrical plates were deployed every 2–3 months in a Thalassia testudinum dominant seagrass bed and nearby barren site to examine seasonal differences in sediment deposition and differences between the vegetated site and the barren site. The data from the plate traps corroborate the reduction of resuspension in the seagrass bed compared to the barren site found in other studies. This result was supported by measurements of reduced near-bed velocity and shear stress in the seagrass meadow. Plate traps had more consistent results than cylindrical traps. Differences between the barren and vegetated sites from the cylindrical traps were variable.